2021
DOI: 10.1039/d1ra02958d
|View full text |Cite
|
Sign up to set email alerts
|

One-pot, ligand-free, room-temperature synthesis of Au/Pd/ZnO nanoclusters with ultra-low noble metal loading and synergistically improved photocatalytic performances

Abstract: Au/Pd/ZnO nanoclusters with ultra-low noble metal loadings were prepared by a one-step and ligand-free method at room temperature. The obtained Au/Pd/ZnO nanoclusters were composed of ZnO nanoclusters decorated with well-dispersed AuPd NPs with ultra-low noble metal loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
(82 reference statements)
2
9
0
Order By: Relevance
“…Regarding the light absorption capacity, the Au/ZC composite exhibited an absorption spectrum spanning the UV light region (λ < 390 nm) and visible light region, with a pronounced peak centered at 564 nm (Figure g). The UV light absorption of the Au/ZC sample originated from the absorption band edge of the ZnO nanostructure, while the absorption in the visible light region arose from surface plasmon resonance (LSPR) of Au NPs. Concerning the recombination rate, the resulting Au/ZC sample exhibited a considerably reduced PL emission in comparison with that of the original ZC sample (Figure h). This outcome can be ascribed to the intrinsic property of metallic Au NPs, which act as efficient electron trappers, facilitating the unrestricted movement of electrons along their surface and/or between the CB and their Fermi level. , This characteristic enhances the separation efficiency of the electron–hole pairs.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the light absorption capacity, the Au/ZC composite exhibited an absorption spectrum spanning the UV light region (λ < 390 nm) and visible light region, with a pronounced peak centered at 564 nm (Figure g). The UV light absorption of the Au/ZC sample originated from the absorption band edge of the ZnO nanostructure, while the absorption in the visible light region arose from surface plasmon resonance (LSPR) of Au NPs. Concerning the recombination rate, the resulting Au/ZC sample exhibited a considerably reduced PL emission in comparison with that of the original ZC sample (Figure h). This outcome can be ascribed to the intrinsic property of metallic Au NPs, which act as efficient electron trappers, facilitating the unrestricted movement of electrons along their surface and/or between the CB and their Fermi level. , This characteristic enhances the separation efficiency of the electron–hole pairs.…”
Section: Resultsmentioning
confidence: 99%
“…A simple room-temperature one-pot synthesis method without any ligand was adopted for synthesis where Au-Pd/ZnO nanocluster manifested high photocatalytic response and stability compared to pure ZnO counterparts. [174] 5. Fabrication of ZnO Plasmonic NSs…”
Section: Cocatalytic Plasmonic System: the Au-pd /Zno Systemmentioning
confidence: 99%
“…Many researchers have reported that noble metal NPs, such as Au, Pt, Ag, Rh, Ni-Pt, Pd, Cu-Pd, and Au-Pd have been reported resulting in enhanced overall photocatalytic activity by enhancing the electron-hole charge separation. [61][62][63][64][65][66][67][68][69][70][71] In this regard, SnS 2 nanostructures were synthesized by hydrothermal method and were in situ decorated with Ni as a cocatalyst having different concentrations of Ni i.e., 1 mol%, 2.5 mol%, 5 mol%, and 10 mol% through a simple thermal reduction method. The detailed physico-chemical characterisation and inuence of Ni loading on SnS 2 towards its photocatalytic performance were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that noble metal NPs, such as Au, Pt, Ag, Rh, Ni-Pt, Pd, Cu-Pd, and Au-Pd have been reported resulting in enhanced overall photocatalytic activity by enhancing the electron–hole charge separation. 61–71…”
Section: Introductionmentioning
confidence: 99%